1965
DOI: 10.1139/m65-044
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Medium for Extremely Halophilic Bacteria

Abstract: A synthetic medium, made up of 15 amino acids, adenylic and uridylic acid, glycerol, asparagine or ammonium chloride, and various salts, has been developed for halophilic bacteria. Halobacterium cutirubrum and Sarcina litoralis grew as well in this medium as in a complex medium containing casein hydrolysate and yeast extract. Growth of Halobacterium halobium, Halobacterium salinarium, and Sarcina morrhuae was slower in the synthetic medium and the final cell densities were not as great as in the complex medium. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

1966
1966
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 8 publications
0
36
0
1
Order By: Relevance
“…This article must therefore be hereby marked "advertisement" in accordance with 18 U. S. C. §1734 solely to indicate this fact. modification (12) of the medium of Sehgal and Gibbons (13 (14).…”
Section: Methodsmentioning
confidence: 99%
“…This article must therefore be hereby marked "advertisement" in accordance with 18 U. S. C. §1734 solely to indicate this fact. modification (12) of the medium of Sehgal and Gibbons (13 (14).…”
Section: Methodsmentioning
confidence: 99%
“…Organisms belonging to the genera Halobacterium, Haloarcula, Haloferax and Halococcus were grown in the synthetic Onishi-McCance-Gibbons medium (OMG medium), pH 6.2 (11). Natronobacterium pharaonis was grown in OMG medium adjusted pH at 9.0.…”
mentioning
confidence: 99%
“…An amino acid mixture is necessary (18), and other organic compounds such as glycerol can stimulate growth (18). Much research has been done on amino acid transport in halobacteria (19), and it was concluded that all amino acids except cysteine were transported through the membrane.…”
mentioning
confidence: 99%